2018
DOI: 10.1037/sgd0000284
|View full text |Cite
|
Sign up to set email alerts
|

Minority stress and life meaning among bisexual adults: The role of religiosity.

Abstract: Research has found that bisexual stress is negatively associated with well-being outcomes, but little research has examined ameliorating factors in these links. The current study explored the relation between bisexual stress-specifically heterosexist discrimination, expectations of rejection, and internalized biphobia-and life meaning among 365 bisexual individuals. Additionally, we sought to examine the potential moderating role of religiosity. We used structural equation modeling to test our hypothesized mod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 76 publications
0
12
0
Order By: Relevance
“…Nonaffirming religious beliefs about one's sexuality may be particularly prone to inducing proximal minority stressors like internalized stigma, because they frequently center on a person's meaning making system (Dahl & Galliher, 2012;Moscardini et al, 2018;Rosenkrantz et al, 2016). For example, religious beliefs commonly frame a person's understanding of themselves, their relationships with others, their purpose in life, and what may This document is copyrighted by the American Psychological Association or one of its allied publishers.…”
Section: Discussionmentioning
confidence: 99%
“…Nonaffirming religious beliefs about one's sexuality may be particularly prone to inducing proximal minority stressors like internalized stigma, because they frequently center on a person's meaning making system (Dahl & Galliher, 2012;Moscardini et al, 2018;Rosenkrantz et al, 2016). For example, religious beliefs commonly frame a person's understanding of themselves, their relationships with others, their purpose in life, and what may This document is copyrighted by the American Psychological Association or one of its allied publishers.…”
Section: Discussionmentioning
confidence: 99%
“…This manifested as shame, a psycho-sociocultural construct defined as a feeling of being flawed and thus unworthy of acceptance, belonging, and love (Brown, 2006). Previous research has found that internalized homophobia or biphobia that may result from rejection is associated with lower levels of life meaning (Moscardini et al, 2018), and this is particularly salient for bisexual people (la Roi et al, 2019). Community connection is an important factor that may result in greater coping in the face of discrimination.…”
Section: Discussionmentioning
confidence: 99%
“…Community connection is an important factor that may result in greater coping in the face of discrimination. However, there is evidence to suggest that religiosity may not buffer bisexual individuals from the deleterious impacts of rejection related to sexual orientation (Moscardini et al, 2018). Collectively, this body of research emphasizes the need to consider the unique lived experiences of mostly heterosexual women in violence prevention and intervention efforts and consider strategies for building community connection for SMW, and survivors in particular, who may or may not feel connected to the LGBQ community.…”
Section: Discussionmentioning
confidence: 99%
“…Bisexual individuals experience internalized biphobia for a myriad of reasons and the perception that their sexual orientation is not legitimate can increase these feelings (Burke & LaFrance, 2018). Internalized biphobia can lead to several negative health outcomes and decreased wellbeing (Moscardini, Douglass, Conlin, & Duffy, 2018). The findings from the present study possibly suggesting that perceptions of the stability of bisexuality as a sexual orientation are changing may impact bisexual individuals' own internalized biphobia (if present), which could lead to heightened feelings of security and comfort when coming out, which can increase bisexual clients' own wellbeing (Moscardini et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, this perception of low trustworthiness may lead bisexual clients to hide their sexual orientation from romantic partners or others in their lives (Bostwick & Hequembourg, 2014). Being unable to "come out" and live authentically in their own sexual orientation can lead to negative health and wellness outcomes (Burke & LaFrance, 2018, Moscardini et al, 2018. Also, just as perceived untrustworthiness of bisexual individuals may make it difficult for heterosexual individuals to initiate romantic relationships with prospective bisexual romantic partners, it may make it difficult for bisexual individuals to initiate relationships with heterosexual partners, limiting the dating pool for bisexual individuals to other bisexual individuals (Bostwick & Hequembourg, 2014).…”
Section: Discussionmentioning
confidence: 99%